Muscle-derived extracellular vesicles improve disuse-induced osteoporosis by rebalancing bone formation and bone resorption. (February 2023) - Huang, Haisen; Ma, Shixing; Xing, Xiaotao; Su, Xiaoxia; Xu, Xun; Tang, Qi; Gao, Xin; Yang, Jian; Li, Maojiao; Liang, Cheng; Wu, Yutao; Liao, Li; et al.
Abstract: Osteoporosis is a highly prevalent skeletal bone disorder worldwide with characteristics of reduced bone mass and increased risk of osteoporotic fractures. It has been predicted to become a global challenge with the aging of the world population. However, the current therapy based on antiresorptive drugs and anabolic drugs has unwanted side effects. Although cell-based treatments have shown therapeutic effects for osteoporosis, there are still some limitations inhibiting the process of clinical application. In the present study, we developed EVs derived from skeletal muscle tissues (Mu-EVs) as a cell-free therapy to treat disuse-induced osteoporosis. Our results showed that Mu-EVs could be prepared easily and abundantly from skeletal muscle tissues, and that these Mu-EVs had typical features of extracellular vesicles. In vitro studies demonstrated that Mu-EVs from normal skeletal muscles could be phagocytized by bone marrow stromal/stem cells (BMSCs) and osteoclasts (OCs), and promoted osteogenic differentiation of BMSCs while inhibited OCs formation. Correspondingly, Mu-EVs from atrophic skeletal muscles attenuated the osteogenesis of BMSCs and strengthened the osteoclastogenesis of monocytes. In vivo experiments revealed that Mu-EVs could efficiently reverse disuse-induced osteoporosis by enhancing bone formation and suppressing bone resorption. Collectively, our results suggest that Mu-EVs may be a potential cell-free therapy for osteoporosis treatment. Statement of significance: Osteoporosis is a highly prevalent skeletal bone disorder worldwide and has become a global health concern with the aging of the world population. The current treatment for osteoporosis has unwanted side effects. Extracellular veiscles (EVs) from various cell sources are a promising candidate for osteoporosis treatment. In the present study, our team established protocols to isolate EVs from culture supernatant of skeletal muscles (Mu-EVs). Uptake of Mu-EVs by BMSCs and osteoclasts influences the balance of bone remodeling via promoting the osteogenic differentiation of BMSCs and inhibiting the osteoclasts formation of monocytes. In addition, exogenous Mu-EVs from normal skeletal muscles are proved to reverse the disuse-induced osteoporosis. We provide experimental evidence that Mu-EVs therapy is a potential cell-free platform for osteoporosis treatment towards clinical application. Graphical abstract: Image, graphical abstract